A study to assess the impact of knowledge about early ambulation on patient’s satisfaction post Percutaneous Coronary Intervention, at tertiary care hospital, karad. - Mahadeo B Shinde, Suraj A. Pawar (International Journal of Advanced Science and Technology, 2020)
Cardiovascular disease (CVD) has become emerging single most important cause of death worldwide. PCI is the gold standard for diagnosis and treatment of coronary heart diseases. There is a lot of variation in the duration of immobilization for patients post PCI. While it is generally agreed that length of time on bed rest is important to prevent post procedural complications, the ideal duration remains unknown.